Triharmonic Curves in Heisenberg Group. Issue 1 (2nd January 2022) - Senoussi, Bendehiba
Abstract: In this paper, we study triharmonic curves in Heisenberg group . We give necessary and sufficient conditions for helices to be triharmonic. We characterize the triharmonic curves in terms of their curvature and torsion.